Parenting styles and socio-economic status as predictors of social adjustment of children with autism in Ibadan, Oyo state, Nigeria (2020)
Autism spectrum disorders (ASD) is a neurobehavioural disorder characterized by difficulty in social and communicative impairments, which usually affect the ability to form relationships. Due to this, parents of children with autism encounter challenges in the process of parenting which influences the home-social adjustment of these children. Thus, the study examined parenting styles and parental socio-economic status as predictors of home-social adjustment of children with autism. This study adopted a descriptive research design of correlational type. Purposive sampling technique was used to select thirty children with Autism Spectrum Disorder. Questionnaires were further used to gather data on parenting style, parental socio-economic status and social adjustment of children with Autism Spectrum Disorder. Data collected were analysed using Pearson's product moment correlation and multiple regression analysis. The result revealed that parental socio-economic status (r = ,8ll,p<0.05), authoritative (r = .546, p<0.05) and permissive parenting styles (r = .648, p<0.05) were significantly correlated with social adjustment. Authoritarian parenting style was negatively and significantly correlated with social adjustment (r = -.425, p>0.05) while permissive parenting style was negatively and not significantly correlated with social adjustment (r = -. 073, p>0.05) among children with ASD. Thus, parenting styles such as authoritative and permissive parenting styles had significant contribution to social adjustment of children with autism while authoritarian and neglectful parenting styles had insignificant contribution to social adjustment of children with autism. Also, parental socio economic status had significant contribution to social adjustment of children with autism. Therefore, parents of children with ASD should adopt positive parenting in order to promote healthy social relationship. Also, parents should be their children advocate by making their needs known to the member of the public.